Adsorption of Polydisperse Polyvinyl Alcohol Molecules on the Surface of Activated Carbons - J. Barkauskas; A. Vinslovaite (Adsorption Science & Technology)
The adsorption of polyvinyl alcohol (PVA) on activated carbons was studied in aqueous solutions. Each batch of activated carbon produced was obtained via a definite number of technological operations using wood as the raw material. The adsorption process was studied using a gel chromatography technique with potentiometric titrations being employed for evaluating the chemical composition of the activated carbons produced. The data obtained from the various activated carbon samples were compared to ascertain the adsorption mechanism. It was concluded that water molecules had a limited influence on the competitive process of polymer adsorption. A rather pronounced negative correlation between the number of phenol functional groups and PVA adsorption capacity was observed, indicating that these groups hindered the adsorption process. Assumptions concerning the role of phenol functional groups were made, taking into account not only the surface heterogeneity but also changes in the electron density of the graphene layers in the carbon substrate.